P53 Expression Is a Strong Marker of Inferior Survival in De Novo Diffuse Large B-Cell Lymphoma and May Have Enhanced Negative Effect With MYC Coexpression: A Single Institutional Clinicopathologic Study. Issue 4 (1st April 2014) - Xie, Yi; Bulbul, Mohmad Ajaz; Ji, Lingyun; Inouye, Casey M.; Groshen, Susan G.; Tulpule, Anil; O'Malley, Dennis P.; Wang, Endi; Siddiqi, Imran N.
Abstract: Objectives: To examine interactions among clinical factors and pathologic biomarkers in predicting the outcome of patients with diffuse large B-cell lymphoma (DLBCL) treated with rituximab-based immunochemotherapy. Methods: In 85 patients treated at a single institution, clinicopathologic variables were analyzed, including the International Prognostic Index (IPI); germinal/nongerminal center phenotype; MYC, p53, BCL2, Ki-67, and Epstein-Barr virus (EBV) expression; and MYC translocation status. Results: In univariate analysis, overall survival (OS) was worse for patients with high IPI scores, nongerminal center phenotype, high MYC and p53 expression by immunohistochemistry, and EBV positivity. In multivariable analysis, p53 expression was the strongest prognostic factor ( P < .05) independent of IPI and cell of origin. A significant positive association between p53 and MYC expression was found. Moreover, coexpression of p53/MYC had an enhanced negative effect on OS independent of BCL2 expression. Conclusions: Immunohistochemical assessment of p53, particularly in combination with MYC, could be useful in identifying a high-risk subgroup of DLBCL.